STATUS OF MARKETING ACTIVITIES ON SELECTED SMALL AND MEDIUM FRUIT PROCESSING ENTERPRISES (SMFPEs) PRODUCTS: A CASE STUDY OF EAST JAVA, INDONESIA - I B Suryaningrat (UNEJ e-Proceeding, 2012)
Indonesia is an agricultural country with significant contribution by agriculture innational GDP. The fruit processing industries have a special role to play in the nationaleconomy. Understanding problems of Small and Medium Fruit Processing Enterprises(SMFPEs) would support its development. With this aim in mind, a study was conductedin five districts in East Java province (Banyuwangi, Jember, Lumajang, Probolinggo andMalang) of Indonesia to assess the development of SMFPEs. The objective of this studywas to investigate real problems faced by SMFPEs especially in marketing aspect. Throughthis study it was found that SMFPEs have to deal with problems relating to the quality andprice competition, limitation of market, marketing skills, distribution, transportation anddamage products. The details of study are explained in this paper.